Molecular targets for tumour progression in gastrointestinal stromal tumours. Issue 2 (14th January 2004) - Koon, N; Schneider-Stock, R; Sarlomo-Rikala, M; Lasota, J; Smolkin, M; Petroni, G; Zaika, A; Boltze, C; Meyer, F; Andersson, L; Knuutila, S; Miettinen, M; et al.
Abstract : Background and aims: The distinction between benign and malignant gastrointestinal stromal tumours (GISTs) is often unclear at the clinical and histopathology levels. GISTs are believed to arise from the stem cells of Cajal. In order to define genetic biomarkers and identify target genes related to GIST progression, we analysed and compared benign and malignant GISTs with verified follow up data using cDNA expression arrays. Methods: Eight genes were frequently overexpressed in malignant GISTs and their overexpression was confirmed using quantitative real time reverse transcription-polymerase chain reaction. These genes included ezrin (villin 2 (VIL2)), collagen 8 alpha 1 subunit (COL8A1), G2/mitotic specific cyclin B1 (CCNB1), high mobility group protein (HMG2), TSG101 tumour susceptibility protein, CENP-F kinetochore protein, protein tyrosine kinase 2 (FAK), and protein kinase DYRK2. To test these genes in a clinical setting, we obtained diagnostic samples of 16 additional GISTs that were classified at diagnosis as benign, malignant, and uncertain malignant potential (UMP). Results: There was remarkable gene overexpression in all malignant GISTs. Statistical analyses revealed significant correlations between overexpression of several gene pairs in malignant GISTs. We found the strongest correlations (ρ>0.70) among the significant correlations (p<0.01) between CCNB1-CENP-F (ρ = 0.87) and CCNB1-FAK (ρ = 0.73). Gene expression of the UMP GISTs suggested two different groups. Three UMP GISTs had gene expression consistent with malignant tumours and their follow up data revealed that indeed these patients had recurrences later on. On the other hand, UMP GISTs that had low gene expression levels continued free of disease for several years. Conclusions: These results provide insight into the oncogenesis of GISTs and suggest that testing the expression profile of a number of genes may segregate GISTs into groups of different tumour behaviour.